Characterization and optimization of the performance of an integrated ultrasonic membrane anaerobic (IUMAS) in treating pome as substrate - Hybat Salih, Mohamed Abdlrhman (2021)
Palm oil mill effluent (POME) is a highly polluting wastewater with high chemical oxygen demand (COD) and biochemical oxygen demand (BOD). These causes severe pollution to the environment, and water resources. Traditional ways of treating POME are disadvantageous from both economic and environmental perspectives. In this Thesis, the potential of an integrated ultrasonic membrane anaerobic system (IUMAS) for the treatment of POME was investigated. The work began with some characterization studies to provide understandings of fundamental issues for wastewater treatment. This research used different organic loading rates from 0.5 to 13 kg/COD/m3/d as a fed to the system, which operated as semi-continuously at mesophilic temperature from 25-35 °C and pressure ranges of 1.5-2 bars. The IUMAS overall efficiency has been evaluated under six steady states and the influent COD varied between 70,000 to 80,000 mg/L. IUMAS depicted better performance as compared to membrane anaerobic system MAS results in treating the palm oil mill effluent, POME as it achieved higher percentage removal efficiencies for COD, BOD, Turbidity and total suspended solids, TSS which are 97%, 80%, 96% and 98.6% respectively. The highest methane gas percentage, CH4 was 84.5%. The POME characterized qualitatively using SEM, EDX and FTIR. IUMAS performed better compared to MAS. Monod, Contois, Chen and Hashimoto kinetics models were used to estimate the performance of IUMAS for POME sludge treatment and the system has shown good prediction and Chen and Hashimoto model has shown the best fittings of 90%. An optimization study for the preparation conditions of the selected optimum parameters for maximum methane gas production was investigated using Response Surface Methodology, RSM. The determining factors such as pH, organic loading rates, OLR, COD, and Hydraulic retention time, HRT were initially screened using 2 level factorial approach. The screening revealed that the effect of screened parameters was significant. Furthermore, the impact of these four operating parameters were investigated using the faced central design techniques. The results presented the optimum conditions for highest methane yield is 88.7% from POME were pH, 6.9; OLR, 6.5kg COD/m3/day, COD, 74,000 mg/L, and HRT, 5 days. The results obtained in this study have exposed the capability of integrated ultrasonic membrane anaerobic system, IUMAS, in treating POME wastewater.